Aluminum-Induced Alterations to the Cell Wall and Antioxidant Enzymes Involved in the Regulation of the Aluminum Tolerance of Chinese Fir (Cunninghamia lanceolata) - Xu, Shanshan; Wu, Lihua; Li, Lingyan; Zhong, Minghui; Tang, Ying; Cao, Guangqiu; Lin, Kaimin; Ye, Yiquan (Frontiers in Plant Science, 2022)
Chinese fir (Cunninghamia lanceolata), which is an important coniferous tree species in China, is mainly planted in acidic soils with toxic aluminum (Al) levels. However, the consequences of Al toxicity and its resistance mechanism in Chinese fir remain largely uncharacterized. In this study, the Al-induced modification and possible role of cell wall in regulating Al tolerance in Chinese fir were investigated by using seedlings with contrasting Al tolerance, namely, Al-sensitive (YX02) and Al-resistant (YX01) genotypes. The results in present work showed that Al treatment resulted in a dose- and time-dependent inhibition of root growth and oxidative damage in both genotypes, but more in YX02 than in YX01. The severe oxidative damage observed in YX02 under Al stress was found to correlate with lower antioxidant enzyme activities as compared with YX01. The greater root growth inhibition observed in YX02 compared with YX01 was associated with a higher accumulation of Al in pectin and hemicllulose 1 (HC1) fraction because of the higher pectin and HC1 contents and the lower degree of pectin demethylation due to enhanced pectin methylesterase activity in YX02, which ultimately enhanced cell wall binding capacity for Al in YX02. Taken together, our results suggested that enhancement of antioxidant enzyme activities and cell wall modification-induced Al exclusion are the two mechanisms responsible for the Al tolerance of Chinese fir.